THE EFFECTIVENESS OF MIND MAPPING TECHNIQUES IN ENHANCING READING COMPREHENSION AND IDEA ORGANIZATION FOR 7 th -GRADE LEARNERS - Po‘latova Farangiz Furqatjon qizi; Azimbayeva Dilafruz Abdujabbarovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article explores the effectiveness of mind mapping as a strategy for  improving  reading  comprehension  and  idea  organization  among  7th-grade students. It discusses the limitations of traditional reading instruction methods and emphasizes the importance of helping learners identify main ideas, supporting details, and  relationships  between  concepts.  Grounded  in  cognitive  learning  theory,  mind mapping is presented as a visually engaging technique that enhances understanding, memory retention, and active participation. The article describes how students who create  mind  maps  during  reading  lessons  demonstrate  improved  comprehension, summarization,  logical  organization,  and  academic  writing  skills.  In  addition  to supporting reading development, mind mapping is shown to be an effective tool for note-taking, essay planning, exam preparation, presentations, and problem-solving. Although  initial  guidance  from  teachers  is  necessary,  consistent  practice  leads  to greater independence and confidence among learners. Overall, the study concludes that mind mapping is a highly beneficial instructional approach that fosters critical thinking, motivation, and long-term academic success. Abstract: This article explores the effectiveness of mind mapping as a strategy for  improving  reading  comprehension  and  idea  organization  among  7th-grade students. It discusses the limitations of traditional reading instruction methods and emphasizes the importance of helping learners identify main ideas, supporting details, and  relationships  between  concepts.  Grounded  in  cognitive  learning  theory,  mind mapping is presented as a visually engaging technique that enhances understanding, memory retention, and active participation. The article describes how students who create  mind  maps  during  reading  lessons  demonstrate  improved  comprehension, summarization,  logical  organization,  and  academic  writing  skills.  In  addition  to supporting reading development, mind mapping is shown to be an effective tool for note-taking, essay planning, exam preparation, presentations, and problem-solving. Although  initial  guidance  from  teachers  is  necessary,  consistent  practice  leads  to greater independence and confidence among learners. Overall, the study concludes that mind mapping is a highly beneficial instructional approach that fosters critical thinking, motivation, and long-term academic success.